Nitrogen dose and placement in conservation agriculture for augmenting cropgrowth, productivity and profitability of Indian mustard (Brassica juncea) - PADHAN, SMRUTI RANJAN; JAT, SHANKAR LAL; SINGH, A K; PARIHAR, C M; POONIYA, VIJAY; KUMAR, SANDEEP; MEENA, M C; RADHESHYAM; KUMAR, ANUP; DARJEE, SIBANANDA (The Indian Journal of Agricultural Sciences, 2023)
Optimization of nitrogen (N) fertilization is vital for minimizing losses and realizing the yield potential of Indian mustard [Brassica juncea (L.) Czern.] under different tillage and residue management options. Hence, a field experiment was conducted during winter (rabi) seasons of 2021–22 and 2022–23 at research farm of ICAR-Indian Agricultural Research Institute, New Delhi to study the effect of nitrogen placement methods under conservation agriculture (CA) for augmenting crop growth, productivity and profitability of Indian mustard. Experiment consisted a split-plot design with three crop establishment practices (CEP) [ZT-R, Zero tillage without residue retention; ZT+R, Zero tillage with residue; CT, Conventional tillage] in main-plots and nitrogen placement methods (NPM) [control (no N); recommended dose of N (RDN)-conventional; RDN-SSB (subsurface band placement of second N split along the crop rows); 80% RDN-SSB] in sub-plots. The ZT+R enhanced crop growth rate by 6.0–36.1% over CT at various crop stages. The ZT+R reported higher soil moisture by 9–20.7% over CT and ZT-R. Significantly superior seed yield (14.3–28.5%), net return (20.5–53.9%) and benefit cost ratio (21.8–79.0%) was obtained with ZT+R over ZT-R and CT while RDN-SSB recorded 7.3–9.1% higher seed yield over other treatments. Statistically at par results were obtained under RDN-conventional and 80% RDN-SSB for yield attributing characters and seed yield delineating that a saving of 20% N in mustard production is possible without compromising yield and this can reduce environmental footprint as well. Therefore, this study concluded that the residue retention under ZT along with subsurface N placement in mustard crop gives better vegetative growth, yield attributes and yield with a potential to save 20% N and can be opted in semi-arid Indo-Gangetic plains and similar agro-ecologies.